Kontribusi Persewaan Tanaman Hias terhadap Pendapatan Produsen Tanaman Hias di Kota Malang dan Sekitarnya - Farah Chalida Hanoum (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
This research aims to obtain an overview of rentals characteristic business ornamental plant of the scale of households and small scales and knowing the contribution rentals ornamental plant of the scale of households and small scales against income producers ornamental plants. The determination of the location of the research done deliberately (purposive) that is implemented in the city of Malang and Batu city with the consideration that location is an ornamental plant production center to continuously ornamental plants rental. Methods of data retrieval method using Census data, the analysis carried out qualitatively and quantitatively. The result of qualitative analysis : First , in the matter of pricing, where the scale of ornamental plants rental households, no price on the basis of plants, but based on the sized manufacturing, while on a small scale in addition to rental based on size is also based on the type of plants. Second, the targert market or tenant. Where on a small scale, ornamental plants rental market target is broader this is due to the partnership business, based on the result, the contribution of revenue each tenancy. The contribution rental income an ornamental against producers an ornamental received household scale of 33,26 percent. While on small scale of 22,90 percent.